(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The Covid-19 Crisis and the Reshaping of Christian Worship Part Three: Church Economics.This essay discusses the economic challenges and financial strain faced by churches in the wake of the COVID-19 crisis. As physical attendance dwindled and traditional fundraising avenues were disrupted, churches encountered a financial crunch that impacted their operational capabilities and the livelihoods of their staff. Exploring the decline in donations, the innovative fundraising strategies adopted, and the long-term implications for church infrastructure, this essay aims to provide a comprehensive understanding of the economic repercussions of the pandemic on religious institutions.